Pengaruh Penambahan Labu Kuning (Cucurbita Moschata) Terhadap Organoleptik, Kapasitas Antioksidan, Nilai Gizi Mie Basah - Anak Agung Ayu Eka Laksmi Dewi; Anak Agung Nanak Antarini; I Gusti Putu Sudita Puryana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
Pumpkin is a food that is rich in Vitamins A and C, minerals, carbohydrates and antioxidants. This pumpkin also contains beta carotene which is quite high (180 SI / g). The aims of this study to determine the effect of adding pumpkin to flour on organoleptic quality, antioxidant capacity and nutrition value of wet noodles. This study uses an experimental research method with the type of RAK which consists of five pumpkin addition treatments namely 10%, 20%, 30%, 40%, 50%. The data was analyzed using ANOVA by using BNT advanced test. The results showed that the addition of pumpkin with white flour significantly affected organoleptic quality which included color, texture, taste, overall acceptance, color quality, texture quality, protein content, carbohydrate content, fat content, water content, ash content and capacity antioxidant but the aroma has no real effect on wet noodles. The best treatment of this study was P3 (30% addition by weight of wheat flour) with characteristics of color quality 1.33 (slightly yellow), texture quality 3.20 (springy), color 3.33 (like), texture 3.21 (likes), aroma 3.41 (likes), taste 3.58 (likes) and overall reception 3.50 (likes) with protein content 6.81% bb, carbohydrate content 23.25% bb, fat content 4.84 % bb, 64.35% moisture content, ash content 0.75% bb and antioxidant capacity 0.75 mg / L GAEAC.Keywords: Wet Noodles, Pumpkin, Antioxidant Capacity, Nutrition Value